Enhanced Bio-Oil Production from Agricultural Waste via NiCl₂-Assisted Pyrolysis: A Comparative Study of Candlenut and Coffee Shells - Yeni Ria Wulandari; Muhammad Arif Firmansyah; Yeni Variyana; Tri Haryono; Vinda Avri Sukma; Sudibyo Sudibyo; Nurjan Didik Purwanto (Jurnal Kimia Sains dan Aplikasi, 2026)
Indonesia’s limited fossil fuel reserves, coupled with increasing national energy demand, highlight the need for alternative and renewable fuel sources. Biomass-derived bio-oil produced through pyrolysis represents a promising solution that can both reduce dependence on petroleum-based fuels and mitigate environmental pollution from underutilized biomass waste. This study investigates the production of bio-oil from candlenut shells and coffee shells through pyrolysis at varying temperatures (250, 350, and 450°C), conducted with and without a NiCl2 catalyst. The bio-oil was characterized for yield, density, and viscosity. The highest bio-oil yields from non-catalytic pyrolysis were achieved at 450°C, amounting to 39.14% for candlenut shells and 41.80% for coffee shells. Catalytic pyrolysis using NiCl2 enhanced the bio-oil yield, producing up to 55.78% (candlenut shells at 450°C) and 58.05% (coffee shells at 350°C). Density measurements showed the highest values in catalytic pyrolysis at 250°C, while the lowest densities were observed in non-catalytic pyrolysis at 450°C. Viscosity followed a similar trend, decreasing with increasing temperature and the presence of the catalyst. FTIR analysis confirmed the presence of functional groups including C–O, C=O, C=C, C≡C, C–H, and O–H. Overall, this study demonstrates the potential of candlenut and coffee shell waste as feasible feedstocks for bio-oil production, offering alternative renewable energy sources for future applications.